Multidimensional Systolic Arrays of LMS Algorithm Adaptive (FIR) Digital Filters - H. AL-Helali, Riyadh A.; R. Al-Hashemy, Bakir A. (Al-Khwarizmi Engineering Journal, 2009)
A multidimensional systolic arrays realization of LMS algorithm by a method of mapping regular algorithm onto processor array, are designed. They are based on appropriately selected 1-D systolic array filter that depends on the inner product sum systolic implementation. Various arrays may be derived that exhibit a regular arrangement of the cells (processors) and local interconnection pattern, which are important for VLSI implementation. It reduces latency time and increases the throughput rate in comparison to classical 1-D systolic arrays. The 3-D multilayered array consists of 2-D layers, which are connected with each other only by edges. Such arrays for LMS-based adaptive (FIR) filter may be opposed the fundamental requirements of fast convergence rate in most adaptive filter applications.